Teacher’s Application of the Communicative Language Teaching (CLT) in Teaching Oral Communication Towards Instructional Strategies - Emma Arana (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The first aim of this descriptive-narrative study is to explore the understandings and attitudes of English teachers of Signal Village National High School regarding adopting Communicative Language Teaching (CLT) in their classroom practices to better understand the appropriateness and effectiveness of Communicative Language Teaching or CLT activities in their classroom teaching practice. The second aim of this research is to investigate and understand the factors that help and hinder secondary teachers’ implementation of CLT in their classrooms. The study has employed nine English teachers in the school where the researcher is currently working for 15 years. The research outcomes and recommendations resulting from this dissertation have the potential to help the English teachers of Signal Village National High School enhance English teaching efficacy in the following areas: it may help them to identify the main impacts of CLT in a local context and this research may provide potential suggestions for English teachers to improve their teaching strategies and to improve students’ communicative competence. Moreover, insights gained from this research may improve the teaching and learning experiences for both teachers and students of Signal Village National High School, Taguig City. The results of this study might also help both teachers and students change from emphasizing grammar-based translation to a communicative approach, which could motivate secondary students to be more focused on communicative activities and improve students’ communicative competence. Lastly, it might assist policy-makers and users to understand the complexity of introducing communicative English teaching into the K to 12 Curriculum.